Study on Time Factors in the Smoke Control Process of Highway Tunnel Fires - Guoping Zheng; Dapeng Xue; Yizhou Zhuang; Yusheng Zhu (Advances in Civil Engineering)
Fire is the most deadly risk during tunnel operation. Early rapid response and a reasonable smoke control plan are very important to evaluate tunnel fire performance. In order to study the relevant time factors for smoke management in a highway tunnel, firstly, the logical sequence and time of the fire alarm system (FAS) startup are investigated and analyzed. Then, according to the one-dimensional fluid mechanics model, the time rule of adjusting the airflow field in the tunnel from the normal operation stage to the emergency ventilation state is analyzed theoretically. Finally, the abovementioned theoretical formulas are verified through the employment of model experiments. The analysis shows that the time that passes from the start of the fire to when the exhaust fan is activated is close to 3 minutes. The time required to form a stable critical wind speed, however, is close to 7 minutes, which is longer than the 5 minutes it takes for the fire to reach its maximum temperature. Due to inertia, it takes about 0.5 to 2 minutes for the air velocity in tunnels of different lengths to drop from the traffic piston wind speed to the critical wind speed. If reverse smoke extraction is required, however, the duration is between 3 and 8 minutes. The conclusion is of guiding significance for the preparation of the emergency linkage control scheme for tunnels, as well as for the setting of initial boundary conditions for CFD fire simulations.